Plk1-dependent and -independent roles of an ODF2 splice variant, hCenexin1, at the centrosome of somatic cells - Soung, Nak-Kyun (2009)
Outer Dense Fiber 2 (ODF2) was initially identified as a major component of the sperm tail cytoskeleton, and was later suggested to be localized to somatic centrosomes and required for the formation of primary cilia. Here, we showed that a splice variant of hODF2 called hCenexin1, but not hODF2 itself, efficiently localizes to somatic centrosomes via an isoform-specific C-terminal extension and recruits Plk1 through a Cdc2-dependent phospho-S796 motif within the extension. This interaction and Plk1 activity were important for proper recruitment of pericentrin and γ-tubulin, and, ultimately, for formation of normal bipolar spindles. Earlier in the cell cycle, hCenexin1, but again not hODF2, also contributed to centrosomal recruitment of ninein and primary cilia formation independent of Plk1 interaction. These findings provide a unique example of how a splice-generated C-terminal extension of a sperm tail-associating protein mediates unanticipated centrosomal events at distinct stages of the somatic cell cycle.